Pengenalan Hijamah sebagai Metode Pendekatan kepada Masyarakat Desa Jonjo Kecamatan Parigi Kabupaten Gowa - Syandri Syandri; Abdil Munzir; Muhammad Saddam Nurdin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
The purpose of the STIBA Makassar Real Work Lecture (KKN) Batch V is as a form of community service which is a pillar of the tridharma of higher education, especially in approaching the community by using thibbunnabawi as the main program. The method of implementing the service program begins with mapping the problems and needs of the community using SOAR analysis. After the analysis is done, a work program that is appropriate and needed by the community is drawn up. Work programs that have been successfully implemented include: Dirasah and tahsin, TPA teaching, Ramadhan safari, and hijamah or cupping. All of these programs managed to run well and have shown results in accordance with the KKN objectives that have been proclaimed, namely an approach to village communities for the sake of religious education for village communities.